Audiological outcome measures with the BONEBRIDGE transcutaneous bone conduction hearing implant: impact of noise, reverberation and signal processing features. (2nd July 2020) - Curca, Ioan A.; Parsa, Vijay; Macpherson, Ewan A.; Scollie, Susan; Vansevenant, Katherine; Zimmerman, Kim; Lewis-Teeter, Jamie; Allen, Prudence; Parnes, Lorne; Agrawal, Sumit
Abstract: Objective: To assess the performance of an active transcutaneous implantable-bone conduction device (TI-BCD), and to evaluate the benefit of device digital signal processing (DSP) features in challenging listening environments. Design: Participants were tested at 1- and 3-month post-activation of the TI-BCD. At each session, aided and unaided phoneme perception was assessed using the Ling-6 test. Speech reception thresholds (SRTs) and quality ratings of speech and music samples were collected in noisy and reverberant environments, with and without the DSP features. Self-assessment of the device performance was obtained using the Abbreviated Profile of Hearing Aid Benefit (APHAB) questionnaire. Study sample: Six adults with conductive or mixed hearing loss. Results: Average SRTs were 2.9 and 12.3 dB in low and high reverberation environments, respectively, which improved to −1.7 and 8.7 dB, respectively with the DSP features. In addition, speech quality ratings improved by 23 points with the DSP features when averaged across all environmental conditions. Improvement scores on APHAB scales revealed a statistically significant aided benefit. Conclusions: Noise and reverberation significantly impacted speech recognition performance and perceived sound quality. DSP features (directional microphone processing and adaptive noise reduction) significantly enhanced subjects' performance in these challenging listening environments.